(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The music genre and its etymology of jazz are discussed. The meaning and importance of musical genres and types are also revealed. Thoughts about the attitude of people in the art life of the 20th century are explained. Art is a unique form of social consciousness and human activity.